Analisis Kearifan Lokal dalam Komunitas Silat Besi Tangerang sebagai Penguatan Civic Culture (Studi Deskriptif pada Komunitas Pencak Silat Besi Kota Tangerang) - Wahyu Puji Rahayu Ningsih; Ria Yuni Lestari; Qotrun Nida (Lembaga Yasin AlSys, 2026)
Silat Besi Tangerang is a cultural heritage of the Betawi ethnic community in Tangerang that not only represents a traditional martial art, but also holds the potential to shape the civic culture of the people of Tangerang City. Local wisdom as an ancestral cultural legacy, including the practice of Silat Besi Tangerang, should be preserved; however, the forces of globalization and the limited scholarly attention to Betawi culture in Tangerang, particularly Silat Besi Tangerang, have posed challenges to its continued existence and preservation. This study aimed to analyze local wisdom within the Silat Besi Tangerang community as an effort to strengthen civic culture in society. The study employed a descriptive approach, with data collected through observations, interviews, and documentation. The findings indicate that the Silat Besi Tangerang community remains active through regular training and sustained involvement in various cultural events in Tangerang City. The strengthening of civic culture is fostered through community participation and the direct involvement of the Silat Besi Tangerang community in diverse social and cultural activities in their surrounding environment. The study concludes that the Silat Besi Tangerang local wisdom community has been able to maintain its existence while simultaneously reinforcing civic culture, thereby ensuring that Silat Besi Tangerang remains relevant and widely recognized in the modern society of Tangerang City.